The Effect of the Canine ABCB1‐1Δ Mutation on Sedation after Intravenous Administration of Acepromazine - D. Deshpande; K.E. Hill; K.L. Mealey; J.P. Chambers; M.A. Gieseg (Journal of Veterinary Internal Medicine, 2016)
Background Dog breeds with the ABCB1‐1Δ mutation have substantially truncated nonfunctional P‐glycoprotein. Dogs homozygous for this mutation (mut/mut) are susceptible to the toxic adverse effects of ivermectin, loperamide, and vincristine. Anecdotal reports suggested ABCB1 mut/mut dogs showed increased depth and duration of acepromazine sedation. Hypothesis/Objectives That ABCB1 mut/mut dogs have increased depth and duration of sedation after acepromazine IV compared to normal dogs (nor/nor). Animals Twenty‐nine rough‐coated collies were divided into 3 groups of dogs based on their ABCB1 genotype: 10 mut/mut, 10 mut/nor, and 9 nor/nor. Methods Dogs were given 0.04 mg/kg of acepromazine IV. Level of sedation, heart rate, respiratory rate, and blood pressure were recorded for 6 hours after acepromazine administration. Area under the curves (AUCs) of the normalized sedation score results were calculated and compared. Results The median sedation scores for ABCB1 mut/mut dogs were higher than nor/nor dogs at all time points and were higher in mut/nor dogs for the first 2 hours. These differences were not found to be significant for any individual time point (P > .05). The median sedation score AUC for mut/mut dogs was significantly higher than nor/nor dogs (P = .028), but the AUC for mut/nor dogs was not (P = .45). There were no significant differences between groups for heart rate, respiratory rate, and blood pressure (P > .05). Conclusions and Clinical Importance In ABCB1 mut/mut dogs acepromazine dose rates should be reduced and careful monitoring performed during sedation.